AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA TAHUN 2017 DI DESA SUMBER PINANG KECAMATAN MLANDINGAN KABUPATEN SITUBONDO CRIMINAL RESPONSIBILITY OF NOTARY ON COUNTERFEITING AUTHENTIC DEED - Rima Sari Febriyanti; Dra. Yulinartati, AK, MM, CA; Elok Fitriyah (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2018)
Research on Accountability of Village Fund Allocation Fund Management in 2017 In Sumber Pinang Village, Mlandingan Sub-District, Situbondo Regency. The objective to be achieved is to describe accountability of planning, implementation, reporting and accountability of management of Village Fund Allocation Year 2017 in Sumber Pinang Village Mlandingan Subdistrict of Situbondo Regency. Discussion in this thesis is about planning, implementation, reporting and accountability of management of Village Fund Allocation Year 2017 in Sumber Pinang Village Mlandingan Subdistrict Situbondo Regency In the writing of this research, the author uses descriptive qualitative research method by describing or describing the state of the subject or object of research. Based on the results of research and data analysis and discussion that has been done then it can be concluded that: (1) Planning of the ADD program (Village Fund Allocation) in the village of Sumber Pinang Mlandingan District Situbondo Regency has gradually implemented the concept of participatory development of village communities; (2) The implementation of the ADD (Village Fund Allocation) program in Sumber Pinang village, Mlandingan Subdistrict, Situbondo District has applied participative, responsive, transparent principles; (3) Accountability of both technical and administrative accounting is good, but in the case of financial administration accountability, the competence of human resource managers is the main obstacle, so it still requires assistance from local government apparatus in order to adjust the rule change every year.